AB1322 Influence of dietary nutrients in prevalence of osteoarthritis (OA) knee. (23rd January 2014) - Sanghi, D.; Raj, S.; Srivastava, R.N.
Abstract : Objectives: There is growing recognition of the importance of nutritional factors in the maintenance of bone and joint health and that nutritional imbalance combined with endocrine abnormalities may be involved in the pathogenesis of Osteoarthritis (OA). The present study sought to identify influence of dietary nutrients in prevalence of Osteoarthritis (OA) knee Methods: A cross sectional study - 150 Subjects were recruited from outpatient clinic with the diagnosis of knee Osteoarthritis (KOA) according to the criteria of American College of Rheumatology (ACR). Controls were age sex matched healthy subjects who were free from disease under study. OA was radiologically graded according to Kellgren-Lawrence (KL) grades. Body Mass Index (BMI) was recorded by standard procedure. Dietary nutrient intakes were analyzed by self administered questionnaire including three day dietary recall and food frequency table (FFQ). Results: An average weight and BMI was significantly higher in subjects with OA knee in comparison to subjects without KOA. Among all dietary factors under study riboflavin, β-carotene, vitamin C and vitamin D was significantly lower in subjects having OA knee in comparison to subjects without OA knee. In unadjusted logistic regression, lower intake quartile of riboflavin, β-carotene, vitamin C and vitamin D having higher risk of OA knee in comparison to higher intake quartiles. However in adjusted analysis, risk of OA knee for riboflavin was diminished and β-carotene lose some strength but vitamin C and D having similar strength of risk of OA knee in quartile having lower intake. As the severity of disease was only defined by vitamin D intake. Conclusions: The present cross sectional study revealed that lower intake of β- carotene, vitamin C and vitamin D intake is risk factor for knee OA. These nutrients might be an explanatory nutrient for the course of OA knee and might lead disease modifying effect Disclosure of Interest: None Declared